Multi-Regression Analysis of Factors Influencing Perceived Academic Writing Competence (PAWC) of Vocational School Students - Lastika Ary Prihandoko; Ana Shohibul Manshur Al Ahmad; Fredy Fredy; Fathu Rahman (IAIN MADURA, 2022)
Most upper-semester students who fail to graduate have an issue with their perceived academic writing competence (PAWC). PAWC is associated with writing self-efficacy (WSE) and writer's block (WB). Thus, improving WSE and decreasing WB are crucial for succeeding in the final project writing of the upper-semester students. Only limited studies focused on exploring academic writing practice for vocational students by survey strategy. This study used a quantitative approach to test the hypothesis that WSE and WB positively affect PAWC. Respondents were selected using random sampling involving 200 students from a vocational school in Surakarta. Respondents filled survey about PAWC, WSE, and WB consisting of 18 items. The hypothesis was tested by multiple regression analysis. The study results revealed that WSE and WB are positively correlated with PAWC. This research implies that faculty members are advised to focus on encouraging WSE and reducing WB to improve AW competence through curriculum improvements. With the increase in students' academic writing skills, the classic problem of late completion of studies due to late writing of the final project can be solved.